Pilot Testing A Community-Based Diabetes Health Promotion Intervention: A Study in a Rural Community in Chiang Mai, Thailand - Peeranuch LeSeure; Benchamat Thatsaeng (Alta Dharma Publisher, 2021)
Introduction: In Thailand, the demand for adult health care has risen due to the rapidly increased prevalence of diabetes mellitus; therefore, it is challenging to successfully implement diabetes management in rural areas due to a shortage of doctors and nurses. Objective: The purpose of this pilot study was to determine the effectiveness of a health promotion intervention developed by community village health volunteers (VHVs). Method: Twenty patients with diabetes and their family support persons living in Talat Khwan Sub-district, Chiang Mai, Thailand, participated in a diabetes health promotion intervention. The intervention consisted of diabetes education, a health campaign, and home visits. The outcomes measured were 1) fasting blood sugar levels (FBS) and 2) family involvement in health promotion behaviors using the Family Involvement Questionnaire. Results: After the intervention, FBS and family involvement were significantly improved (ES = 1.40, t = 2.76, p < .05) and ES = 1.65, t = 3.82, p < .001, respectively), indicating that the diabetes health promotion intervention improved glycemic control and enhanced family involvement. Recommendation: Further study is needed to determine the sustainability of diabetes health-promoting behaviors as a result of the intervention